Relationship between Physical Activity with Sleep Quality in The Pandemi Time of Yarsi University Students Class of 2020 and The Review According to The Islamic Point of View - Ari Fajar Maulana; Miranti Pusparini; Endy Muhammad Astiwara (Junior Medical Journal, 2023)
Sleep is one of the basic human needs, meaning that humans naturally need sleep as a daily necessity. Sleep quality is influenced by many things, one of which is physical activity. The Covid-19 pandemic has made students spend a lot of time at home which allows them not to do physical activity. This study aims to determine the relationship between physical activity and sleep quality of students at the medical faculty of YARSI University. This research is a correlational study with a cross sectional design. The population of this study were YARSI University medical faculty students class of 2020. The sampling technique was purposive sampling. The total sample is 142 students. Physical activity instruments using the Global Physical Activity Questionnaire and the Pittsburgh Quality Sleep Index as sleep quality instruments. Data analysis using Chi Square with a confidence level of 95%. The results of the chi square analysis obtained a value (p) = 0.013 and Odd Ratio (OR) = 3.097. These results indicate that there is a significant relationship (p0.05) between physical activity and sleep quality. Subjects who are active in physical activity have the opportunity to get good quality sleep 3,097 times higher than subjects who are not active.